2006
DOI: 10.1111/j.1365-263x.2006.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental plaque formation and salivary mutans streptococci in schoolchildren after use of xylitol‐containing chewing gum

Abstract: The results suggest that chewing gum with xylitol or sorbitol/maltitol can reduce the amount of dental plaque and acid production in saliva in schoolchildren, but only the xylitol-containing gum may also interfere with the microbial composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
49
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 24 publications
9
49
0
1
Order By: Relevance
“…Three months after the end of the chewing period, no significant difference was found between the 2 groups. These results were expected, and reinforce previous findings [Mäkinen et al, 1989;Holgerson et al, 2007].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Three months after the end of the chewing period, no significant difference was found between the 2 groups. These results were expected, and reinforce previous findings [Mäkinen et al, 1989;Holgerson et al, 2007].…”
Section: Discussionsupporting
confidence: 83%
“…The interdental plaque pH was recorded in a group of children submitted to different xylitol chewing gum exposures. Previously, 6 g in a single dose was demonstrated to produce significantly less reduction in pH, after a sucrose 5% rinse, in comparison to a lower dosage [Holgerson et al, 2007]. The data from the present study show that xylitol chewing gum appears to be capable of producing a reduction in oral MS in children at high risk of caries.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…4,10,[26][27][28][29]31 However, xylitol also reduces both biofilm and S. mutans levels when added to a patients' diet as a sweetener, thus preventing early development of caries. 11,13,32,33 The results found in the present study corroborate these findings, since groups G1 (XYL) and G2 (CHX + XYL) showed enhanced reduction in biofilm levels in the sixth month compared to other groups (p <0.05).…”
Section: Discussionsupporting
confidence: 88%
“…Ksilitol, sorbitol ya da maltitollü sakız çiğ-nenmesinin çürüklü ve çürüksüz olarak ayırılan 7-12 yaşındaki okul çocuklarında plak miktarı ve tükürük asit yapımını azalttığı; ancak sadece ksilitollü sakız (günlük dozu 6.18 g) çiğnemesi-nin MS ve total bakteri sayısında anlamlı azalmaya yol açtığı saptanmıştır (7) . Azalmanın çürüksüz çocuklarda daha belirgin olduğu bulunmuştur.…”
Section: Discussionunclassified